P422Cardiac ischemic stress during remote ischemic preconditioning. (15th July 2014) - Abdul Ghani, S; Angelini, GD; Suleiman, MS
Abstract: Background: Remote ischemic preconditioning (RIPC) induced by brief ischemia/reperfusion (I/R) cycles of remote organ (e.g. limb) is cardio-protective. The myocardial cellular changes during RIPC that are responsible for this phenomenon are not currently known. However, it is widely accepted that unlike classical ischemic preconditioning, RIPC does not induce ischemic stress in the myocardium. To address this issue we developed a novel RIPC mouse model and monitored myocardial changes in energy-rich phosphates. Methods: Treatment of animals and all procedures were in accordance with Home office guidance (Scientific Procedures) Act of 1986. Male C57/Bl6 mice were anesthetized by an intra-peritoneal injection of Tribromoethanol. A suitably designed cuff was placed around the hind limb and inflated at 200mmHg to prevent blood flow as confirmed by Laser Doppler Flowmetry. RIPC was induced by 4 cycles of 5min of limb ischemia followed by 5min of reperfusion. Hearts were extracted and used for either measurement of metabolites or perfused in the Langendorff mode. Injury and recovery of function were obtained for RIPC and sham operated mice. Myocardial metabolites (e.g. adenine and guanine nucleotides and by-products) from excised hearts following RIPC were extracted and measured using HPLC. Results: RIPC significantly reduces infarct size (34% vs. 59%; P<0.05), total creatine kinase release and end diastolic tension following I/R. RIPC was associated with significant ischemic stress as shown by a fall in ATP/AMP (1.324± 0.124 vs. 0.965± 0.036 P<0.05), ATP/ADP (0.917 ± 0.03 vs. 0.805± 0.025 P<0.05 ), GTP/GMP (2.71± 0.162 vs. 2.019± 0.103 P<0.005) and GTP/GDP (0.87 ± 0.017 vs. 0.749± 0.021 P<0.005 ). There was also a significant increase in myocardial adenosine (0.21± 0.032 vs. 0.127± 0.01 nmol/mg wet weight, P<0.05). Conclusions: RIPC is associated with myocardial ischemic stress. This effect is likely to contribute to RIPC-induced protection against sustained ischemic insult.